Studi Kekuatan momen lentur Tiang Pancang Group Terhadap Beban Tumbukan Pada Breasthing Dolphin Dengan kapal tanker 50.000 Dwt di lamongan oil tanker terminal - Bambang Kiswono (Universitas Muhammadiyah Surabaya, 2017)
Study analysis planning and design pile group, impact force from berthing tankers 50.000DWT, breasthing dolphins require so that absorb by horizontal and vertical loading, this pile resistance deflects a distance of y1 at a depth of z1. Type structure design terminal jetty with impact lateral breasthing dolphin and mooring dolphin. This pile cap with case-in- place concrete Materials for steel pipe pile in jetties with ASTM A252 Grade 3 out side diameter 800mm thick 16mm and out side diameter 900mm thick 12mm,length pile consist 2 joint are connected,bottom 12m, middle12m,upper12m soil test laboratory result from ITS using bor log BH2 appropriate location jetty. Analysis the main parameter to take from the soil ia a reaction modulus by modelled P-Y curve.with program Group 8 (Ensoft, 2010) Using absorb fender from trelleborg marine or sumitomo marine.. type SCN 1400 ,E = 139 Tm, R =163 T this loading at the fix head of pile resistance bending moment The final result ϕ=900mm,t=9mm and ϕ=800mm,t=12mm maintenance by cathodic.protection to enable them resist corrosion in sea water.